2019
DOI: 10.1177/1055665618824432
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Hypernasality, Intelligibility, and Language and Reading Skills in 10-Year-Old Children With a Palatal Cleft

Abstract: Background: This study investigated the associations between hypernasality and intelligibility, and language and reading skills in 10-year old children with a cleft palate ± lip. Design: Cross-sectional data collected during routine assessments of speech and language in a centralized treatment setting. Participants: Children aged 10, born with cleft palate ± lip from 4 birth cohorts (N = 123). Outcome Measures: Hypernasality and intelligibility: Swedish Articulation and Nasality Test-N; language: Language 6-16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Additional effects of cleft type on speech and hearing issues require further investigation. Recently, measures of hypernasality and reduced intelligibility were associated with a higher risk of reading and language problems, including poorer comprehension (Saervold et al, 2019).…”
Section: Isolated Clefts and Academic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Additional effects of cleft type on speech and hearing issues require further investigation. Recently, measures of hypernasality and reduced intelligibility were associated with a higher risk of reading and language problems, including poorer comprehension (Saervold et al, 2019).…”
Section: Isolated Clefts and Academic Performancementioning
confidence: 99%
“…Speech issues are a risk factor for reading impairments and dyslexia in general, but research for children with iCL/P is mixed. Some studies have found relationships between speech and reading impairments (Chapman, 2011; Særvold et al, 2019), while others have not (Conrad et al, 2014; Conrad, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have evaluated the potential impact of early hearing loss or disrupted speech (Særvold et al, 2019; Chapman, 2011b). Although these are key factors in developing academic skills, other researchers continue to find differences after controlling for speech or hearing (Shriver et al, 2006; Hentges et al, 2011; Conrad et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two studies on linguistic ability in 10-year-olds with CLP have been published [33,34]. In a study by Boyce et al [33], a total of 37 participants with non-syndromic orofacial clefts, aged 7; 1-14; 1 years, were matched to 129 non-cleft peers regarding age, gender and maternal education.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were seen in expressive and receptive language skills. According to Saervold et al [34], 123 10-year-olds with non-syndromic CP, without developmental or attention difficulties, displayed scores regarding sentence recall, serial recall, and vocabulary within normal ranges. Speech problems in children with CLP as a group decrease with increasing age [35], and it may be that in non-syndromic children with CLP, scores on linguistic tests normalizes as speech normalizes.…”
Section: Discussionmentioning
confidence: 99%